2005
DOI: 10.1097/01.aco.0000168329.10067.1a
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetics and the rate corrected interval: learning from droperidol?

Abstract: Droperidol can lead to serious cardiac arrhythmias from QT prolongation. Recent advances in the pathophysiology of congenital and acquired long QT syndrome are reviewed. Preclinical tests assessing potential new drugs for QT prolongation are briefly discussed. Considerations for the management of these patients during perioperative phases are explored. The optimal treatment of the long QT syndrome is presented along with a glimpse into future possibilities in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(121 reference statements)
1
3
0
Order By: Relevance
“…In Group T we observed significant heart rate lowering (expressed as prolongation of the RR interval) without a parallel change in uncorrected QT time, which may explain why significant changes were seen only for QT cb , whereas QT cf and QT cF remained unchanged. In addition, parallel reductions in TDR induced by thoracic epidural anaesthesia were observed and this may augment our hypothesis about the anti‐arrhythmic properties of thoracic epidural anaesthesia, in particular that there is a strong correlation between changes in TDR and torsadogenic drug action 16,21 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In Group T we observed significant heart rate lowering (expressed as prolongation of the RR interval) without a parallel change in uncorrected QT time, which may explain why significant changes were seen only for QT cb , whereas QT cf and QT cF remained unchanged. In addition, parallel reductions in TDR induced by thoracic epidural anaesthesia were observed and this may augment our hypothesis about the anti‐arrhythmic properties of thoracic epidural anaesthesia, in particular that there is a strong correlation between changes in TDR and torsadogenic drug action 16,21 …”
Section: Discussionsupporting
confidence: 71%
“…Although prolongation of the QT c interval is known to be a risk factor for ventricular arrhythmias, it is not the sole determinant of an agent's potential to cause TdP. It is believed that a parallel increase in the TDR in particular predisposes patients to torsadogenic drug action 16 . Sympathetic blockade of the heart resulted in a reduction in TDR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we observed that laryngoscopy and tracheal intubation provoked QTc prolongation without significant changes in the T peak – T end time [22]; we concluded that this may explain the extremely low incidence of TdP in connection with intubation, in spite of the observed increase in repolarisation time. The ability to reduce TDR is characteristic of thiopental, a drug that prolongs QTc time, and explains the safe usage of this barbiturate in individuals with long QT syndrome [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are reports of a decreased duration of corrected QT after this procedure [15]. The observed prolongation of the period of ventricle repolarisation following laryngoscopy and intubation could be related to increased activity of the sympathetic system and increased catecholamine release [7, 16, 17]. Apart from alterations of electrophysiological parameters, these phenomena are often accompanied by an increase in heart rate and arterial blood pressure.…”
mentioning
confidence: 99%